Morphine-3-Glucuronide, Physiology and Behavior - Gabel, Florian; Hovhannisyan, Volodya; Berkati, Abdel-Karim; Goumon, Yannick (Frontiers in Molecular Neuroscience, 2022)
Morphine remains the gold standard painkiller available to date to relieve severe pain. Morphine metabolism leads to the production of two predominant metabolites, morphine-3-glucuronide (M3G) and morphine-6-glucuronide (M6G). This metabolism involves uridine 5′-diphospho-glucuronosyltransferases (UGTs), which catalyze the addition of a glucuronide moiety onto the C3 or C6 position of morphine. Interestingly, M3G and M6G have been shown to be biologically active. On the one hand, M6G produces potent analgesia in rodents and humans. On the other hand, M3G provokes a state of strong excitation in rodents, characterized by thermal hyperalgesia and tactile allodynia. Its coadministration with morphine or M6G also reduces the resulting analgesia. Although these behavioral effects show quite consistency in rodents, M3G effects are much more debated in humans and the identity of the receptor(s) on which M3G acts remains unclear. Indeed, M3G has little affinity for mu opioid receptor (MOR) (on which morphine binds) and its effects are retained in the presence of naloxone or naltrexone, two non-selective MOR antagonists. Paradoxically, MOR seems to be essential to M3G effects. In contrast, several studies proposed that TLR4 could mediate M3G effects since this receptor also appears to be essential to M3G-induced hyperalgesia. This review summarizes M3G’s behavioral effects and potential targets in the central nervous system, as well as the mechanisms by which it might oppose analgesia.